Crafting an audience: UX writing, user stylization, and the symbolic violence of little texts. (August 2022) - Portmann, Lara
Abstract: To date, little attention has been paid to how producers of digital media complicate notions of participation and audience in digital media. Taking the work of user experience (UX) writers as a case study, I offer an analytic framework for approaching the conceptual challenges that come with this. The empirical focus of my analysis is an emblematic example of UX writers' work: the ubiquitous microcopy (i.e. user interface texts) produced for cookie consent notices. Orienting to Jones's (2020b) work on digital and algorithmic pragmatics, I demonstrate how these "little texts" act in ways which are both agentful and influential. More than a matter of implicit audience design (Bell, 1984 ), UX writers actively use the affordances of software interfaces for inventing, stylizing, and crafting an audience. It is through this strategic stylizing of users that UX writers produce what Bakhtin (1986) calls a superaddressee. By positioning users in particular ways – and in particular moments – these little, seemingly inconsequential texts of digital media can thus effectively exercise a form of symbolic violence.